Premature Coronary Artery Disease and Plasma Levels of Interleukins; a Systematic Scoping Review and Meta-Analysis - Haji Aghajani, Mohammad; Toloui, Amirmohammad; Ahmadzadeh, Koohyar; Madani Neishaboori, Arian; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2022)
Introduction: Interleukins (ILs) can act as a predictive indicator of Premature Coronary Artery Disease (pCAD) and may be useful in screening of high-risk patients. However, there is no consensus on the relationship of serum levels of ILs and pCAD, yet. As a result, this study has been conducted in order to review the literature on the relationship between serum levels of different ILs and pCAD. Methods: Medline, Scopus, Embase, and Web of Science databases were searched until December 7th 2020. Two reviewers independently screened and summarized eligible articles. A meta-analysis was performed to assess the relationship of ILs and pCAD. Results: 12 case-control articles were included. IL-6 plasma changes do happen in pCAD patients with a standardized mean difference (SMD) of 0.51 (95% CI: 0.12-0.90; p=0.010) compared with the control group. This difference was also observed when evaluating the plasma levels of IL-1 and IL-17, with an SMD of 1.42 (95% CI: 1.11-1.73; p<0.001) and 0.59 (95% CI: 0.14-1.04; p=0.011), respectively. Meanwhile, no significant difference existed in plasma levels of IL-10 (SMD=0.26; 95% CI: -0.17-0.70; p=0.236), and IL-18 (SMD=1.44; 95% CI: -0.19-3.07; p=0.083) between pCAD patients and those in the control group. Conclusion: Low level of evidence showed that there may be a significant relationship between increased plasma levels of ILs and the occurrence of pCAD. As a result, prospective cohort studies with serial assessments of serum ILs during follow up period, focusing on controlling classical risk factors of pCAD and increase in level of ILs, should be conducted.